Strategic Leadership and Time Efficiency: Analyzing the Economic Impact on Employee Performance in Widhya Asih Children's Social Welfare Institutions across Bali's Regencies - Sudarnaya, I Ketut; Ernawati, Ketut Ayu Ely; Rizky, Muhammad (Yayasan Riset dan Pengembangan Intelektual, 2025)
The purpose of this study is to determine how the performance of staff members at the Widhya Asih Children's Social Welfare Institute in Bali Province is impacted by time management, competency, and leadership style. This study employs a quantitative methodology, gathering data via questionnaire distribution. An interval scale with a ra nge of 1 to 5 was used to measure the questionnaireA random sample was employed to pick the respondents, and a maximum of 33 respondents were used. SPSS Version PASW Statistics 18 for ewindows is the data analysis method utilized to support this study. The results of hypothesis testing on all variables show that the factors influencing (1) time management have a significant effect on employee performance. (2) Competence has a negative but considerable impact on employee performance. (3) Leadership style has a fav orable and significant impact on employee performance. (4) Employee Performance is significantly impacted by leadership style, competence, and time management.